2016
DOI: 10.1038/srep24705
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-based Signature of Gingivitis Treatments: A Randomized Study

Abstract: Plaque-induced gingivitis can be alleviated by various treatment regimens. To probe the impacts of various anti-gingivitis treatments on plaque microflora, here a double blinded, randomized controlled trial of 91 adults with moderate gingivitis was designed with two anti-gingivitis regimens: the brush-alone treatment and the brush-plus-rinse treatment. In the later group, more reduction in both Plaque Index (TMQHI) and Gingival Index (mean MGI) at Day 3, Day 11 and Day 27 was evident, and more dramatic changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(90 citation statements)
references
References 36 publications
6
84
0
Order By: Relevance
“…Additionally, we found no intra‐group effects on tested microbiome parameters after 4 weeks in the HA as well as in the AmF/SnF 2 group (Figures and ). This observation is also supported by another microbiota‐based study by Huang et al . Here, a decrease in alpha and beta diversity was found only, after applying additionally an AmF/SnF 2 ‐containing mouthwash together with the AmF/SnF 2 toothpaste …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Additionally, we found no intra‐group effects on tested microbiome parameters after 4 weeks in the HA as well as in the AmF/SnF 2 group (Figures and ). This observation is also supported by another microbiota‐based study by Huang et al . Here, a decrease in alpha and beta diversity was found only, after applying additionally an AmF/SnF 2 ‐containing mouthwash together with the AmF/SnF 2 toothpaste …”
Section: Discussionsupporting
confidence: 85%
“…Additionally, we found no intra-group effects on tested microbiome parameters after 4 weeks in the HA as well as in the AmF/SnF 2 group (Figures 3 and 4). This observation is also supported by another microbiota-based study by Huang et al 30 Here, a decrease in alpha and beta diversity was found only, after applying additionally an AmF/SnF 2 -containing mouthwash together with the AmF/SnF 2 toothpaste. 30 Although the fluoride ion of AmF/SnF 2 itself has only limited antimicrobial effects, it has been proposed that the amine portion of AmF possesses surface-active properties and can prevent bacterial adhesion as well as inhibit bacterial growth.…”
Section: No Differential Effects On Microbiota Composition Between supporting
confidence: 83%
See 1 more Smart Citation
“…Emerging evidence suggests that clusters of bacteria, rather than individual species, might be of use as diagnostic markers for each disease; and that bacterial functions (e.g., proteolysis, flagellar assembly, bacterial motility) may be a more robust discriminant of disease than species. While these early novel findings support a gene‐centric rather than a species‐centric approach to disease causation, further studies are required to better characterize such bacterial clusters and gene functions and to validate their potential use both as a diagnostic tool and as response to treatment monitoring tool …”
Section: Methodsmentioning
confidence: 99%
“…They were also recovered from oral plaque of guinea pigs [21] and feces of piglets [54], dental plaque from healthy individuals, plaque and saliva from patients with various types of caries, gingivitis, chronic periodontitis, and peri-implantitis [23,2527,34,35,37,38,44,45,47,49,52,59,60,62,6669,91,94], decayed tooth surfaces and discordant caries from intact enamel surfaces [53]. Leptotrichia species were also isolated from bronchoalveolar lavage fluid, and patients with leukocytosis, hypoxemia, and dyspnea [24].…”
Section: Brief Additional Clinical Information On Leptotrichia Speciesmentioning
confidence: 99%